2018
DOI: 10.3390/atmos9110439
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Atmosphere–Ocean Forcings Outside the Tropical Pacific on the El Niño–Southern Oscillation Occurrence

Abstract: The El Niño–Southern Oscillation (ENSO) is the strongest interannual air–sea coupled variability mode in the tropics, and substantially impacts the global weather and climate. Hence, it is important to improve our understanding of the ENSO variability. Besides the well-known air–sea interaction process over the tropical Pacific, recent studies indicated that atmospheric and oceanic forcings outside the tropical Pacific also play important roles in impacting and modulating the ENSO occurrence. This paper review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 127 publications
0
11
0
Order By: Relevance
“…On one hand, tropical processes, including the positive airsea interaction [1] and oceanic dynamics [2], play an important role for the ENSO occurrence. On the other hand, more and more recent studies have demonstrated that atmospheric and oceanic forcings outside the tropical Pacific also play crucial role in modulating onset, development, and amplitude of the ENSO events, such as the North Pacific Oscillation (NPO; an intrinsic atmospheric variability over the extratropical North Pacific) [3,4], Aleutian Low [5], Arctic Oscillation (AO; the dominant atmospheric variability over the extratropical Northern Hemisphere) [6,7,8], North Atlantic SST [9], East Asian monsoon variability, the atmospheric circulation anomalies in the Southern Hemisphere, and the SST variability over the Indian and Atlantic Oceans [10]. For instance, Vimont et al [3] and Chen et al [4] showed that, via seasonal footprinting mechanism, NPO can exert significant impacts on the outbreak of ENSO events.…”
mentioning
confidence: 99%
“…On one hand, tropical processes, including the positive airsea interaction [1] and oceanic dynamics [2], play an important role for the ENSO occurrence. On the other hand, more and more recent studies have demonstrated that atmospheric and oceanic forcings outside the tropical Pacific also play crucial role in modulating onset, development, and amplitude of the ENSO events, such as the North Pacific Oscillation (NPO; an intrinsic atmospheric variability over the extratropical North Pacific) [3,4], Aleutian Low [5], Arctic Oscillation (AO; the dominant atmospheric variability over the extratropical Northern Hemisphere) [6,7,8], North Atlantic SST [9], East Asian monsoon variability, the atmospheric circulation anomalies in the Southern Hemisphere, and the SST variability over the Indian and Atlantic Oceans [10]. For instance, Vimont et al [3] and Chen et al [4] showed that, via seasonal footprinting mechanism, NPO can exert significant impacts on the outbreak of ENSO events.…”
mentioning
confidence: 99%
“…2a). This winter NPO-related tripole SST anomaly pattern bears (Chiang and Vimont 2004) and the spring Arctic Oscillation (Nakamura et al 2006(Nakamura et al , 2007Chen et al 2014Chen et al , 2018a. Significant negative SST anomalies can also be seen in the tropical southern Pacific around 5°-20°S and 120°-170°W.…”
Section: Npo-enso Relationship In Observation and Canesm2mentioning
confidence: 73%
“…In addition, more and more studies showed that the extratropical atmosphere-ocean forcing also plays important roles in modulating the occurrence and amplitude of ENSO events (e.g. Vimont et al 2001Vimont et al , 2003aNakamura et al 2006;Alexander et al 2010;Chen et al 2014Chen et al , 2017Chen et al , 2018aZhang et al 2018;Luo et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Song [22] demonstrated that the winter AO and Siberian High (SH) intensity both contribute to the SAT anomalies corresponding to the first EOF mode primarily through the wind-generated horizontal temperature advection. Note that several studies indicated that the AO's impacts on the global climate systems (such as East Asian winter monsoon, El Niño-Southern Oscillation) are unstable [33][34][35][36]. For example, Li et al [33] found that impact of the winter AO on the East Asian winter monsoon underwent a significant interdecadal change around the early 1980s.…”
Section: Introductionmentioning
confidence: 99%